FACTORS AFFECTING TAXPAYER COMPLIANCE IN PAYING P-2 LAND AND BUILDING TAX IN SUBANG DISTRICT SUBANG REGENCY - Ligarnisa Sabrina S; Indah Umiyati; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Tax revenue has an important role in the development of the country, one of which is to support public facilities and the interests of the community. This shows that the state as much as possible can reduce the role of aid from abroad without having to rely on foreign debt. The country's development efforts will lead to an increase in the community's economy and an increase in the rate of economic growth. Therefore, it would be better if the community participates in paying taxes as an obligation and their involvement in government funding and administration. The purpose of this study was to examine the Factors Affecting Taxpayer Compliance in Paying Land and Building Taxes P-2 in Subang District, Subang Regency, The results of this study conclude that partially income, awareness, religiosity and tax service variables have no effect on taxpayer compliance. While the socialization and SPPT variables have an effect on taxpayer compliance. Simultaneously all variables of income, socialization, SPPT, awareness, religiosity, and service tax authorities affect the variable of taxpayer compliance.